Three Recent Decisions on Repair, Refill and Recycle - Heath, Christopher (Zeitschrift für Japanisches Recht, 2007)
Trade Mark Act Sec. 37 – “Ink Bottle” Where trade-marked ink bottles are commercially refilled by third parties and no indication is given about such alteration of the original goods, such act infringes the trade mark at least in cases where the refilled bottles are not returned to the same customers from which they were obtained. Tokyo High Court, 31 August 2004 – Case No. Hei 15 (Ne) 899 (Riso kagaku kôgyô kabushiki kaisha v. Takken Corporation, et al.) Japanese Trade Mark Act Sec. 38 – “Brother Ink Ribbon” Use of the indication “For brother” (“buraza-yô”) on spare parts for fax machines without consent of the trade mark owner does not qualify as a trade mark infringement in the absence of any confusion as to the origin of the spare parts. Tokyo High Court, 13 January 2005 – Case No. Hei 16 (Ne) 3571 (Brother K.K. v. Ohm Electric Inc.) Patent Act Sec. 101 (1) (i) – “Canon Inkjet Printer” The refilling of patented ink cartridges is an act of infringement both regarding the product patent of the ink tank and the process patent for the manufacture of ink tanks. IP High Court, Special Division (Grand Panel) 31 January 2006 – Case No. Hei 17 (Ne) 10021 (Canon Inc. v. Recycle Assist Co., Ltd.)